Writing Spaces Web Writing Style Guide - Barton, Matt; Kalmbach, James; Lowe, Charles; Open Textbook Library (Open Textbook Library, 2011)
The Writing Spaces Web Writing Style Guide was created as a crowdsourcing project of Collaborvention 2011: A Computers and Writing Unconference. College writing teachers from around the web joined together to create this guide (see our Contributors list). The advice within it is based on contemporary theories and best practices. While the text was originally written for students in undergraduate writing classes, it can also be a suitable resource for other writers interested in learning more about writing for the web. This document is available as a web text for reading online, a printer-friendly PDF, and an EPUB ereader versions.
Introduction -- Writing in the Genres of the Web -- The Rhetorics of Web Pages
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Rhetoric -- Textbooks